Anatomy of the generative structures of the Subantarctic flowering plant Colobanthus apetalus (Labill.) Druce - Milarska, Sylwia; Androsiuk, Piotr; Giełwanowska, Irena (Polish Polar Research, 2021)
This study investigated the details of the morphological and anatomical structure of the generative organs of the Subantarctic flowering plant, belonging to the family Caryophyllaceae - Colobanthus apetalus (Labill.) Druce. The research material was collected in hostile natural conditions in Subantarctic regions, and also was grown in the incubators and the greenhouse of the University of Warmia and Mazury in Olsztyn (Poland). C. apetalus forms tufts with soft and grassy leaves and small greenish flowers that are more obvious than in other Colobanthus species. C. apetalus forms open (chasmogamic) flowers in greenhouse cultivation. The flowers most often form five stamens with two microsporangia. Over a dozen pollen grains are formed in each microsporangium. Studies of the plant material originated from natural conditions conducted by means of a light microscope, have shown that the ovules of the analyzed representative of the genus Colobanthus are anatropous, crassinucellar, and the monosporic embryo sac develops according to the Polygonum type (the most common type in angiosperms). C. apetalus plants underwent a full development cycle in greenhouse cultivation and produced fertile, perispermic seeds. During the C. apetalus growth in conditions at increased air humidity, the vivipary was also observed.